Odpowiedź :
a)
3x -2y= 0| *3
6y -10x- 4 =0
9x-6y=0
6y-10x=4
-x=4
x=-4
3*(-4) -2y=0
-12-2y=0
-2y=12|:(-2)
y=-6
b)
-x+ 2y =-3|*2
2x -4y= 0
-2x + 4y=-6
2x-4y=-6
0=0
równanie tożsamościowe
3x -2y= 0| *3
6y -10x- 4 =0
9x-6y=0
6y-10x=4
-x=4
x=-4
3*(-4) -2y=0
-12-2y=0
-2y=12|:(-2)
y=-6
b)
-x+ 2y =-3|*2
2x -4y= 0
-2x + 4y=-6
2x-4y=-6
0=0
równanie tożsamościowe
3x-2y=0
6y-10x-4=0
3x-2y=0(x3)
-10x+6 y=4
9x-6y=0
-10x+6y=4
-x=-4(-1)
x=4
3(4)-2y=o
12-2y=0
-2y=-12(:-2)
y=6
-x+2y=-3(.2)
2x-4y=0
-2x+4y=-6
2x-4y=o
y=-6
2x-4(-6)=o
2x=24
x=12
6y-10x-4=0
3x-2y=0(x3)
-10x+6 y=4
9x-6y=0
-10x+6y=4
-x=-4(-1)
x=4
3(4)-2y=o
12-2y=0
-2y=-12(:-2)
y=6
-x+2y=-3(.2)
2x-4y=0
-2x+4y=-6
2x-4y=o
y=-6
2x-4(-6)=o
2x=24
x=12